DHUKU TU LENGGE LIMA BUDAYA PERKAWINAN ENDOGAMI SUKU LIO (Studi Kasus Di Kelurahan Wolojita, Kecamatan Wolojita, Kabupaten Ende, Flores NTT) - Raudatul J. Mbejo Golu; Masrokhin (JOURNAL SAINS STUDENT RESEARCH, 2024)
Originating from one of the marriage practices that is still carried out by the people of Wolojita Village, namely Endogamous Marriage (Dhuku Tu Lengge Lima) which is a marriage culture of the Lio tribe which requires marriage between sisters to maintain blood purity and continue to protect ancestral inheritance. So, to find out the background to the occurrence of this case, the author formulates the problem into 3, namely (1) How is the marriage of Dhuku Tu Lengge Lima in Wolojita Village, (2) The factors that cause the marriage of Dhuku Tu Lengge Lima in Wolojita Village and (3) What is the view of Islamic law regarding the marriage of Dhuku Tu Lengge Lima. This research uses a qualitative field method using an empirical normative approach, where data is obtained using 3 methods, namely observation, interviews and documentation so that researchers can conclude the factors that drive the occurrence of Dhuku Tu Lengge Lima, namely because; factor of maintaining the purity of offspring, safeguarding family property, as well as the factor of matchmaking, it is known that according to Islamic law itself there is no prohibition on men and women who have a fraternal cousin relationship from getting married. Therefore, Endogamous Marriage (Dhuku Tu Lengge Lima), whether between uncle's children or aunt's children; may marry each other and the marriage is valid.